Maternal and child health nursing : care of the chilbearing & childrearing family - Pilliteri, Adele (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 1999)
A guide to maternal and child health nursing. This edition maintains its family focus, emphasizing wellness and illness as family-centred events, and using a nursing process framework. Each chapter contains objectives, key terms, key points and critical thinking questions.
Unit 1: Maternal and child health nursing practice -- Unit 2: The nursing role in preparing families for childbearing and childrearing -- Unit 3: The nursing role in caring for families during normal pregnancy, birth, the postpartum, and newborn period -- Unit 4: The nursing role in caring for a family during a complicaton of pregnancy, birth, or the postpartal period -- Unit 5: The nursing role in health promotion for a childrearing family
Includes bibliographical references.
Keywords: MATERNITY NURSING